Molecular identification and phenotypic study of a novel HBB: c.-23A>G mutation in the 5’ untranslated region - Shen, Shichun; Huang, Jungao; Qi, Haimei; Liu, Zezhang; Zhang, Wenqian; Yuan, Xianping; Zhang, Zhuling; Chen, Haijun; Xie, Xinxing; Xiao, Lin; Chen, Junkun; Song, Liyun (Frontiers in Medicine, 2025)
Backgroundβ-thalassemia is a prevalent genetic disorder in the Gannan region, Southern China. Mutations in the 5′ untranslated region of the β-globin gene are associated with diverse clinical phenotypes, posing challenges for effective prevention strategies in this region.MethodsIn this study, carriers of the HBB: c.-23A>G mutation were identified from a cohort of 192,720 individuals who underwent thalassemia gene testing in the Gannan region. Hematological data from these carriers were collected, and pedigree information was gathered for further analysis.ResultsAmong the 192,720 individuals tested, 75 carriers of the HBB: c.-23A>G mutation were identified, yielding a carrier frequency of 3.89 per 10,000. Statistical analysis showed no significant differences in hematological parameters between HBB: c.-23A>G heterozygotes and normal individuals. Furthermore, the minimum free energy of mRNA with the HBB: c.-23A>G mutation showed no significant difference compared to that of the wild-type mRNA.ConclusionThe carrier frequency of HBB: c.-23A>G in the Gannan region is non-negligible. Hematological data analyses suggested that this mutation may be a likely benign variant. Overall, this study elucidates the molecular and phenotypic characteristics of the HBB: c.-23A>G mutation, providing crucial evidence for genetic counseling in clinical practice.